PSYCHOLOGICAL ADJUSTMENT TO AMPUTATION: VARIATIONS ON THE BASES OF SEX, AGE AND CAUSE OF LIMB LOSS - Ali, Shaista; Haider, Syeda Kaniz Fatima (Journal of Ayub Medical College Abbottabad, 2017)
Background: Amputation is the removal of a limb or part of a limb by a surgical procedure in order to save the life of a person. The underlying reasons behind the occurrence of this tragic incidence may be varied. However, irrespective of its cause limb loss is associated with wide range of life challenges. The study was done to investigate the psychological sequel of an individual after losing a limb and to know the level of strain and pressure they experience after this traumatic event. It also attempts to examine the moderating role of some demographic traits such as age, sex and cause of limb loss in psychosocial adjustment to amputation. Methods: The study includes 100 adult amputees of both genders and the data was collected from major government and private hospitals of Peshawar district. Demographic data sheet was constructed in order to know the demographics traits of amputees and a standardize Psychological Adjustment Scale developed by Sabir (1999) was used to find out the level of psychological adjustment after limb loss. Results: Nearly all the amputees' exhibit signs of psychological maladjustment at varying degrees. Males showed much greater signs of maladjustment than women and young adults were much psychologically shattered and disturbed as a result of limb loss. Amputation caused by planned medical reasons leads to less adjustment issues as compared to unplanned accidental amputation in which patient were not mentally prepare to accept this loss. Conclusion: Psychological aspect of amputation is an important aspect of limb loss which needs to be addressed properly in order to rehabilitate these patients and helps them to adjust successfully to their limb loss Keywords: Amputation; Psychological aspect; Adjustment; limb loss; demographic traits; anxiety; Stress